(untitled) (International Journal of Management and Sustainability, 2019)
It is proved from the literatures that, perceptual factors have a great influence on employees’ job performances in organization. The current study tried to sort out some crucial perceptual factors affecting employees’ job performance. The study developed 28 perceptual items based on FGD and literature analysis such as decision making, learning, orientation, training, engagement, evaluation policy etc. Then a proposed perceptual model had been developed. A structured questionnaire was surveyed among the selective respondents (n=500); then tested the items’ reliability and passed (α = .789); after that, the study went for exploratory factor analysis (EFA). Total seven (7) factors (Perceived HR practice; Perceived performance appraisal; Perceived supervisor’s quality & leadership; Perceived work environment & climate; Perceived organizational support; Perceived work pressure; and Perceived compensation plan) were identified. Finally, in confirmatory factors analysis (CFA) testing, one of those factors named Perceived compensation plan (PCP) fall short to pass the validity from the model.